Studi Netnografi Tinjauan Efektivitas Konsultasi Keuangan Dan Akuntansi Pada Aplikasi Quora Bagi Para Pelaku UMKM - Mauliyah, Nur Ika; Sugiarto, Warga Baroka (Wacana Equiliberium (Jurnal Pemikiran Penelitian Ekonomi), 2023)
One of the drivers of economic growth in Indonesia cannot be separated from the involvement of the influence of MSMEs. The reality in Indonesia, MSMEs have not paid attention to the importance of financial accounting knowledge and do not use accounting information in running a business. The purpose of this study is to utilize social media, namely the Quora application that can be used by MSME actors as business finance and accounting consulting for their business ventures. This study uses the netnographic method for the constructivist paradigm that depends on the reality that is formed in society. It is not how someone sends a message, but from the communicator or communicant to form and exchange meaning. The findings show that Quorawan's questions revolve around consulting the importance of financial management for MSMEs, android applications or software that can be used for MSME financial bookkeeping, MSME taxes that must be reported, the application of SAK EMKM by MSMEs, neat accounting records for MSMEs, sharing knowledge of accounting for MSME development, and so on. SAK EMKM is much simpler for MSMEs to implement, compared to SAK ETAP. Financial and accounting consultations are constructivist in nature, depending on the reality formed by the Quorawans as MSME actors in the Quora application. This study recommends that the central government and local governments appreciate financial reports on MSMEs that are constructivist and based on SAK EMKM compiled by the Indonesian Institute of Accountants (IAI).